Conducting Composites: Clay‐Graphene Nanoplatelets Functional Conducting Composites (Adv. Funct. Mater. 41/2016). (2nd November 2016) - Ruiz‐Hitzky, Eduardo; Sobral, Maria Madalena C.; Gómez‐Avilés, Almudena; Nunes, Claudia; Ruiz‐García, Cristina; Ferreira, Paula; Aranda, Pilar
Abstract : On page 7394, E. Ruiz‐Hitzky and co‐workers report on the assembly of graphene nanoplatelets with clay minerals by sonomechanical treatment. The process allows for the incorporation of various supplements, thereby providing access to low‐cost electrically conducting materials with a wide range of other predesigned properties.